RELAÇÕES ENTRE PRÁTICAS DE GESTÃO DO CONHECIMENTO, CAPACIDADE ABSORTIVA E DESEMPENHO NA ÁREA DE MANUTENÇÃO: ESTUDO DE CASO DE UMA INDÚSTRIA AUTOMOBILÍSTICA DO ABC PAULISTA - ZYRIANOFF, WLADMIR (2019)
This research aims to analyze the relations between knowledge management practices, absorptive capacity and performance in the maintenance area of an automotive industry of ABC São Paulo, thus identify and understand how knowledge management and absorptive capacity have been used to improve performance and quality in the maintenance area. As knowledge is one of the high value intangible assets for management of modern organizations, it becomes a differential in creating competitive advantage by the companies, even more nowadays, because the current economic crisis impacts directly on the survival of companies. The methodology used for the elaboration of this work was the qualitative research, through the use of the case study method, through a data source, with the conduction of individual and face-to-face semi-structured interviews, in October and November of 2018, in addition to non-participatory observations made in November and December, and evaluation of documents, records and physical artifacts made during the same period. Seven managers of the company surveyed were interviewed, four of them managers and three engineers. Through the analysis and triangulation of data, it was confirmed that managers perceive the need for knowledge management in maintenance, that the knowledge management practices related to Strategic Management of Knowledge, Organizational Culture, Human Resource Management, Organizational Structure and Information and Communication Technology influence the absorptive capacity. It was also observed that the realized absorptive capacity directly influences the performance and quality of the maintenance area. It was also verified that performance and quality are influenced by knowledge. Therefore, it is understood that knowledge management practices are the most relevant because they influence the absorptive capacity, performance and quality